Alex Cross, Run - Patterson, James, 1947-; Boatman, Michael, 1964-; Boyer, Steven (New York : Hachette Audio, 2013)
In the aftermath of a disgraced plastic surgeon's release from prison, Detective Alex Cross investigates the murder of a young mother whose newborn has disappeared, a case that is further complicated by two additional killings.
Unabridged.
Compact discs.
Read by Michael Boatman and Steven Boyer.
Keywords: Cross, Alex (Fictitious character) -- Fiction; African American detectives -- Fiction; Washington (D.C.) -- Fiction; Suspense fiction; Audiobooks